Resilience in farm technical efficiency and enabling factors: Insights from panel farm enterprise surveys in Kazakhstan and Uzbekistan - Takeshima, Hiroyuki; Djanibekov, Nodir; Abduvalieva, Nilufar; Mirkasimov, Bakhrom; Akramov, Kamiljon T. (International Food Policy Research Institute, 2023)
Economic resilience within the agrifood system is becoming increasingly crucial for assuring sustainable development. This is particularly so in regions with volatile and fragile environments, including Central Asia. Evidence remains scarce regarding what factors can enhance the economic resilience of agents within the agrifood system, including the resilience of productivity and technical efficiency. We partly fill this knowledge gap using the unique panel datasets of farm enterprises in Uzbekistan and southern Kazakhstan, collected in 2019 and 2022, during which these enterprises experienced significant economic shocks in input prices. Using novel methods that combine Inverse Probability Weighting and panel stochastic frontier analyses models, we show that farmers who received more agricultural training and who had been granted greater autonomy in their production decisions in 2018 experienced greater resilience in technical efficiency despite the need to reduce the use of chemical fertilizer and oil/diesel in response to their price surges. Our findings suggest that providing critical public goods like information (related to training) and enabling environment (related to decision-making autonomy) can potentially enhance the resilience in the technical efficiency of farm enterprises. Furthermore, with chemical fertilizer and oil/diesel being potentially environmentally harmful inputs, these farmers also indirectly demonstrated resilience toward environmental sustainability.